Forming professional competence of future engineers-teachers is in the process of learning the professionally-oriented disciplines (Pedagogy of Higher and Secondary Education, 2014)
Filimonova I. А. Forming professional competence of future engineers-teachers is in the process of learning the professionally-oriented disciplines.Modern food production requires not only a high level of education and skills of professionals, but also commitment to innovation and to continuous improvement. One of the effective areas of modernization of education in vocational pedagogy is recognized competency based approach, which aims at developing in the future engineer-teacher professional competence and the formation of appropriate skills.
Keywords: food production; professional competence; engineer; teacher; professional activity; core competencies